Electromagnetic wave absorbing finishing liquid, preparation method thereof, and flexible electromagnetic protection film and application thereof

CN123021631APending Publication Date: 2026-10-30NINGBO JIFENG AUTO PARTS
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610914702.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-24
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

但单一碳纳米管仅具有介电损耗能力,阻抗匹配性能差,电磁波容易在材料表面发生强烈反射而无法进入内部,导致吸波效率低、有效带宽窄,难以满足实际应用要求

Benefits of technology

1、本发明通过特殊工艺一步法制备得到碳纳米管包覆银/钴双金属纳米粒子,实现了银钴纳米粒子的均匀包覆和高度分散,粒径可控在1~20nm。在该双金属体系中,纳米钴粒子提供了强大的磁损耗能力,而纳米银粒子凭借其电导率大幅增强了材料的介电损耗;更为重要的是,在这种特殊的包覆结构中,银、钴金属粒子与碳纳米管的碳骨架之间形成了大量密集的微观异质结界面(碳-银、碳-钴、银-钴界面),能产生强的界面极化和偶极子极化弛豫损耗。使得防护膜在2~18GHz宽频段内实现高吸波效率。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123021631A_ABST
    Figure CN123021631A_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of electromagnetic material protection, and relates to an electromagnetic wave absorption finishing liquid, a preparation method thereof, a flexible electromagnetic protection film and application. The electromagnetic wave absorption finishing liquid comprises carbon nanotube coated silver / cobalt bimetallic nanoparticles, which are prepared by the following method: in a thermal plasma device, silver powder and cobalt powder are mixed and pressed into a block as a catalyst target material, a high-purity graphite rod is used as a cathode, vacuum is drawn, then carbon source and condensing gas are introduced, and the reaction is carried out under the conditions of a working current of 20-40 A and a voltage of 90-100 V; the carbon nanotube coated silver / cobalt bimetallic nanoparticles are obtained. The carbon nanotube coated silver / cobalt bimetallic nanoparticles are prepared by a one-step method, and the wave absorption performance of the material is improved by the action among the carbon nanotube, silver and cobalt.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of electromagnetic material protection technology, and relates to an electromagnetic wave absorbing finishing liquid, its preparation method, a flexible electromagnetic protection film, and its application. Background Technology

[0002] With the rapid development of electronic information technology, electronic components are constantly evolving towards integration, miniaturization, and high frequency, leading to electromagnetic interference and radiation that have become significant issues affecting public health. Electromagnetic radiation not only interferes with the normal operation of electronic equipment, causing signal distortion and equipment malfunctions, but also poses potential harm to human health. Therefore, the development of high-performance electromagnetic protection materials has become an urgent need in the fields of electronic information, national defense, and civilian protection.

[0003] Currently, commercially available high-frequency electromagnetic wave absorbing materials internationally are mainly ferrites and their composites. Their absorption mechanism is primarily based on magnetic loss, and they are often used in the sub-1GHz frequency band. According to the Snoke limit, the saturation magnetization of ferrite materials cannot be arbitrarily increased, and the correlation between the resonant frequency and permeability of ferrite materials leads to a sharp decrease in permeability at high frequencies. Therefore, with the upgrading of electronic devices, the "bottleneck" problem of reduced electromagnetic loss capability of ferrites at high frequencies (GHz) has become prominent. More importantly, in integrated circuits and electron beam accelerators, charged particles that cannot be dissipated in time easily accumulate on the surface of ferrite absorbing patches, accumulating a large amount of static charge, causing them to lose their electromagnetic wave absorption capability. Moreover, when the absorbed energy density is too high, the absorbing patch cannot dissipate heat in time, causing the temperature to rise, which can easily lead to stress mismatch with the substrate and cracking.

[0004] To address the aforementioned issues with ferrite materials, carbon nanotubes, due to their excellent conductivity, large specific surface area, and lightweight properties, have been widely studied as electromagnetic wave absorption and shielding materials. However, single carbon nanotubes only possess dielectric loss capability and poor impedance matching performance. Electromagnetic waves are easily and strongly reflected at the material surface and cannot penetrate the interior, resulting in low absorption efficiency and narrow effective bandwidth, making it difficult to meet practical application requirements. Furthermore, existing microwave absorbing material formulations often use organic solvents as dispersion media, which not only pollutes the environment but also suffers from poor film flexibility and low adhesion, limiting their application in flexible protection fields. Summary of the Invention

[0005] To address the aforementioned problems in the prior art, the present invention aims to provide an electromagnetic wave absorbing finishing liquid, its preparation method, a flexible electromagnetic shielding film, and its application, thereby overcoming the shortcomings of the prior art.

[0006] The present invention employs the following technical solutions to achieve its objective: The present invention provides an electromagnetic wave absorbing finishing liquid, which, by weight, comprises the following components: 10-20 parts of carbon nanotube-coated silver / cobalt bimetallic nanoparticles, 50-60 parts of polyurethane resin emulsion, 20-30 parts of acrylic resin emulsion, 0.5-1 parts of sodium carboxymethyl cellulose, 2-4 parts of curing agent, 2-5 parts of polyvinylpyrrolidone, 0.1-0.5 parts of defoamer, and water.

[0007] Preferably, the curing agent is one or a mixture of isocyanate, 1,4-butanediol and polyether polyol.

[0008] Preferably, the defoamer is one or a mixture of emulsified silicone oil, polyoxypropylene glycerol ether, polyoxypropylene polyoxyethylene glycerol ether, and polydimethylsiloxane.

[0009] Preferably, the solid content of the polyurethane resin emulsion is 20-50 wt%, and the solid content of the acrylic resin emulsion is 20-50 wt%. This invention employs a compound system of polyurethane resin emulsion and acrylic resin emulsion. The waterborne polyurethane resin film exhibits good flexibility and flexural strength after formation, while the introduction of the acrylic resin emulsion effectively enhances the surface adhesion and mechanical strength of the film. The combination of these two components as a binder not only forms a dense polymer cross-linked network under the action of a curing agent, locking carbon nanotube-encapsulated silver / cobalt bimetallic nanoparticles within a three-dimensional system, but also, the entire process is water-based, environmentally friendly, and does not generate chemical solvents.

[0010] Preferably, the carbon nanotube-coated silver / cobalt bimetallic nanoparticles are prepared by the following method: The reaction is carried out in a thermal plasma device. A mixture of silver and cobalt powder, pressed into a block, is used as the anode catalyst target. A high-purity graphite rod is used as the cathode. A vacuum is drawn, followed by the introduction of a carbon source and condensate gas, maintaining a working pressure ≤0.05 MPa. The thermal plasma reaction is conducted under conditions of a working current of 20-40 A and a voltage of 90-100 V. After the reaction, the product is collected, yielding carbon nanotube-coated silver / cobalt bimetallic nanoparticles. The pressing process involves pouring the uniformly mixed powder into a mold using an isostatic press and pressing it into a block under a pressure of 10-40 MPa for 2-8 minutes.

[0011] This invention directly uses a mixture of silver and cobalt powder as an independent target material. Within a high-temperature plasma region, the silver-cobalt mixed target material is uniformly vaporized, generating bimetallic atomic vapor. Simultaneously, the carbon source gas is decomposed into active carbon atoms. Under the quenching effect of the condensing gas, cobalt acts as a catalyst, guiding the carbon atoms to dissolve and precipitate on its surface, growing into carbon nanotubes. Silver, in turn, works synergistically with cobalt, adhering to the tube wall, thus forming a complete three-dimensional heterostructure of "carbon nanotube-coated silver / cobalt" in a one-step process. The operating current and voltage are the core parameters for controlling the morphology and particle size of the carbon nanotube-coated silver / cobalt bimetallic nanoparticles. In the early stages, the inventors conducted numerous preliminary experiments, determining the optimal ranges for the operating current and voltage as follows: current 20-40A and voltage 90-100A. Under these parameters, the plasma energy density is moderate, and silver / cobalt micron powder can be stably decomposed into 1~20nm nanoparticles. The carbon source is fully decomposed and carbon nanotubes with complete structure and uniform diameter are directionally grown on the surface of the bimetallic particles. The effects of Co, Ag and carbon nanotubes are maximized, so that the carbon nanotubes coating silver / cobalt bimetallic nanoparticles achieve the best microwave absorption performance.

[0012] In the preparation process of carbon nanotube-coated silver / cobalt bimetallic nanoparticles: preferably, the average particle size D50 of the silver powder and cobalt powder are independently 10~50μm; the mass ratio of silver powder to cobalt powder is 1:1~4; the purity of the silver powder and cobalt powder is ≥99.9wt%; the purity of the high-purity graphite rod is ≥99.99wt%; and the vacuum is drawn to 1*10 -2 Pa~9*10 -3 Pa; the carbon source is one or more of ethanol, methane, ethylene, and acetylene, and the condenser is argon and / or helium; the partial pressure of the carbon source is 0.02~0.04 MPa, the partial pressure of the condenser is 0.01~0.02 MPa, and the thermal plasma reaction time is 10~60 min.

[0013] Preferably, in the carbon nanotube-coated silver / cobalt bimetallic nanoparticles, the particle size range of the silver and cobalt particles is 1-20 nm, more preferably 2-15 nm. The preparation method of the present invention can obtain silver and cobalt particles with a particle size range of 1-20 nm, and the silver and cobalt composite within this particle size range maximizes the electromagnetic wave absorption capability.

[0014] A second aspect of this invention provides a method for preparing an electromagnetic wave absorbing finishing liquid, comprising the following steps: (1) Dissolve polyvinylpyrrolidone in water and stir until homogeneous; (2) Disperse the defoamer and curing agent in water and stir until homogeneous; (3) Pour the mixture from step (2) into the mixture from step (1), add sodium carboxymethyl cellulose to dissolve it completely; add polyurethane resin emulsion and acrylic resin emulsion in sequence and mix evenly; finally add carbon nanotube-coated silver / cobalt bimetallic nanoparticles and stir to disperse them initially. (4) The above mixture is subjected to high pressure homogenization to obtain a uniformly dispersed slurry, which is the electromagnetic wave absorption finishing liquid.

[0015] Preferably, the high-pressure homogenization step includes: first, pressureless homogenization for 10-40 minutes, followed by high-pressure dispersion at 800-1800 bar for 20-80 minutes. This process of first pressureless homogenization and then high-pressure homogenization facilitates the uniform dispersion of carbon nanotube-coated silver / cobalt bimetallic nanoparticles.

[0016] A third aspect of this invention provides a flexible electromagnetic shielding film, which is prepared by the following steps: (1) Dissolve polyvinylpyrrolidone in water and stir until homogeneous; (2) Disperse the defoamer and curing agent in water and stir until homogeneous; (3) Pour the mixture from step (2) into the mixture from step (1), add sodium carboxymethyl cellulose to dissolve it completely; add polyurethane resin emulsion and acrylic resin emulsion in sequence and mix evenly; finally add carbon nanotube-coated silver / cobalt bimetallic nanoparticles and stir to disperse them initially. (4) The above mixture is subjected to high-pressure homogenization to obtain a uniformly dispersed slurry, which is the electromagnetic wave absorption finishing liquid. (5) Apply the electromagnetic wave absorbing finishing liquid onto the substrate and dry it. The resulting coating layer is the flexible electromagnetic protection film.

[0017] Preferably, the drying temperature is 80~100℃ and the time is 5~20min.

[0018] The thickness of the flexible electromagnetic shielding film is not limited and can be flexibly set according to actual product requirements.

[0019] The fourth aspect of this invention provides an application of a flexible electromagnetic shielding film in electromagnetic radiation protection products.

[0020] Compared with the prior art, the present invention has the following beneficial effects: 1. This invention utilizes a special one-step process to prepare carbon nanotube-coated silver / cobalt bimetallic nanoparticles, achieving uniform coating and high dispersion of the silver / cobalt nanoparticles with a controllable particle size of 1–20 nm. In this bimetallic system, the cobalt nanoparticles provide strong magnetic loss capability, while the silver nanoparticles significantly enhance the dielectric loss of the material due to their high conductivity. More importantly, in this special coating structure, numerous dense microscopic heterojunction interfaces (carbon-silver, carbon-cobalt, silver-cobalt interfaces) are formed between the silver and cobalt metal particles and the carbon framework of the carbon nanotubes, generating strong interfacial polarization and dipole polarization relaxation losses. This enables the protective film to achieve high absorption efficiency in a wide frequency band of 2–18 GHz.

[0021] 2. The electromagnetic wave absorbing finishing liquid of the present invention adopts a water-based polyurethane and acrylic resin composite binder system, combined with sodium carboxymethyl cellulose thickener and polyvinylpyrrolidone dispersant to construct an environmentally friendly and non-toxic water-based formulation system. The prepared protective film has excellent flexibility, adhesion and mechanical strength, which solves the problems of environmental pollution and poor film-forming performance of traditional organic solvent-based formulations.

[0022] 3. The protective film prepared by this invention consumes electromagnetic waves absorbed into the material in the form of magnetic resonance and releases them into the air in the form of heat. It can be widely used in the fields of protection such as electronics, fire protection, human body protection, and vehicle interior protection, and has broad prospects for industrialization. Attached Figure Description

[0023] Figure 1 The electron microscope image and elemental energy spectrum of the carbon nanotube-coated silver / cobalt bimetallic nanoparticles of this invention are shown. Figure 2 This is a photograph of the actual flexible electromagnetic shielding film of the present invention; Figure 3 The images show the reflection loss (RL) curves of various embodiments and comparative samples of the present invention. Detailed Implementation

[0024] In the description of this invention, unless otherwise stated, the numerical range "a~b" represents a shortened representation of any combination of real numbers between a and b, and includes both a and b. "Multiple" includes two or more types, and can be two, three, four, five, or more.

[0025] The technical solution of the present invention will be further described and illustrated below with reference to specific embodiments and accompanying drawings. It should be understood that the specific embodiments described herein are only for the purpose of helping to understand the present invention and are not intended to limit the specific scope of the present invention. Furthermore, the accompanying drawings used herein are merely for better illustrating the content disclosed in the present invention and do not limit the scope of protection. Unless otherwise specified, the raw materials used in the embodiments of the present invention are all commonly used in the art, and the methods used in the embodiments are all conventional methods in the art.

[0026] In the following examples and comparative examples, the sources of raw materials are as follows: Polyvinylpyrrolidone: Shanghai Jizhi Biochemical Technology Co., Ltd., K19; Sodium carboxymethyl cellulose: 2000 mPa·s; Polyurethane resin emulsion: solid content 35 wt%; Acrylic resin emulsion: solid content 35 wt%; Silver micron powder: D50 is 10-50μm, purity is 99.9wt%; Cobalt micron powder: D50 is 10-50μm, purity is 99.9wt%.

[0027] In the following examples and comparative examples, the briquetting step is as follows: the uniformly mixed powder is poured into a mold using an isostatic press, and the powder is pressed into briquetting material under a pressure of 20 MPa for 5 minutes. Example 1

[0028] The electromagnetic wave absorbing finishing liquid in this embodiment is composed of the following components: 14g of carbon nanotube-coated silver / cobalt bimetallic nanoparticles, 50g of polyurethane resin emulsion, 30g of acrylic resin emulsion, 0.5g of sodium carboxymethyl cellulose, 2g of trimer isocyanate, 3g of polyvinylpyrrolidone, 0.5g of polyoxypropylene glycerol ether, and 60g of water.

[0029] The carbon nanotube-coated silver / cobalt bimetallic nanoparticles were prepared by the following steps: The process was conducted using a thermal plasma device. First, silver micron-sized powder and cobalt micron-sized powder were mixed at a mass ratio of 1:2 and pressed into blocks to serve as the anode catalyst target. A high-purity graphite rod (99.999%) was used as the cathode. The reactor was evacuated to a background vacuum of 5*10⁻⁶. -3 After Pa, methane gas was introduced as a carbon source (partial pressure 0.02 MPa), and argon gas was introduced as a condenser (partial pressure 0.01 MPa). The reaction was carried out for 30 minutes at a working current of 20 amperes and a working voltage of 90 volts. After the reaction was completed, the powder was collected to obtain the target product.

[0030] The flexible electromagnetic shielding film provided in this embodiment is prepared by the following method: (1) Take a 1L empty beaker and add 50g of deionized water. Weigh 3g of polyvinylpyrrolidone (PVP) powder with an analytical balance and add it to the beaker. Stir for 4min to dissolve the PVP powder in the water.

[0031] (2) Add 10g of deionized water to a small beaker, weigh 0.5g of polyoxypropylene glycerol ether and add it to the beaker, then weigh 2g of trimer isocyanate and add it to the small beaker. Stir for 1 minute to make the polyoxypropylene glycerol ether and trimer isocyanate evenly dispersed in the water. Pour the mixture in the small beaker into the large beaker in step (1) and stir for 1 minute.

[0032] (3) Weigh 0.5g of sodium carboxymethyl cellulose and add it to a large beaker. Stir for 4 minutes to dissolve it completely. Then weigh 50g of polyurethane resin emulsion and add it to the beaker. Next, weigh 30g of acrylic resin emulsion and add it to the beaker. Stir for 10 minutes to mix all the additives in the large beaker thoroughly. Finally, weigh 14g of carbon nanotube-coated silver / cobalt bimetallic nanoparticles and pour them into the large beaker. Stir for 5 minutes to initially disperse the nanotubes.

[0033] (4) Turn on the power supply of the high pressure homogenizer circulating water, turn on the power supply of the homogenizer, pour the mixture from step (3) into the feed cup of the homogenizer, turn on the start button, first homogenize without pressure for 20 minutes to eliminate large agglomerates in the mixture, then pressurize at 1200 bar for high pressure dispersion for 50 minutes until the homogenized liquid appears mirror black and shiny, then stop the dispersion; export the homogenized dispersion slurry for later use.

[0034] (5) Turn on the coating machine and the vacuum switch. Place the PET film on the coating machine's worktable, adjust the gap between the doctor blade and the PET film, pour the dispersed slurry onto the PET film, and start the coating process. Turn on the heating switch to heat the PET film to 100°C and dry the slurry for 10 minutes. Remove the dried PET film and peel off the coating layer on its surface to obtain the flexible electromagnetic protective film prepared in this embodiment, with a thickness of 1.7 mm. A photograph of the film is shown below. Figure 2 As shown. Example 2

[0035] The composition of the electromagnetic wave absorbing finishing liquid and the preparation method of the flexible electromagnetic shielding film in Example 2 are the same as in Example 1. The thickness of the flexible electromagnetic shielding film is 1.7 mm.

[0036] The carbon nanotube-coated silver / cobalt bimetallic nanoparticles of Example 2 were prepared by the following steps: The process was conducted using a thermal plasma device. First, silver micron-sized powder and cobalt micron-sized powder were mixed at a mass ratio of 1:2 and pressed into blocks to serve as the anode catalyst target. A high-purity graphite rod (99.999%) was used as the cathode. The reactor was evacuated to a background vacuum of 5*10⁻⁶. -3 After passing through a pressure of 0.02 MPa, methane gas was introduced as a carbon source, and argon gas was introduced as a condenser gas (partial pressure of 0.01 MPa). The reaction was carried out for 30 minutes at a working current of 30 amperes and a working voltage of 95 volts. After the reaction was completed, the powder was collected to obtain the target product.

[0037] Electron microscopy images of the carbon nanotube-coated silver / cobalt bimetallic nanoparticles prepared in this embodiment are shown below. Figure 1 As shown, Figure 1 The image on the left is at a scale of 100 nm, and the image on the right is an elemental energy spectrum analysis of the nanoparticles. Figure 1 As can be seen, the black dots are silver / cobalt nanoparticles, which are spherical with a particle size between 5 and 10 nm, and the particles are fully dispersed or coated between carbon nanotubes. The energy spectrum on the right shows that the nanoparticles contain three elements: carbon (C), silver (Ag), and cobalt (Co), proving that the nanoparticles prepared in the experiment are carbon nanotube-coated silver / cobalt bimetallic nanoparticles. Example 3

[0038] The electromagnetic wave absorbing finishing liquid in this embodiment is composed of the following components: The composition includes 18g of carbon nanotube-coated silver / cobalt bimetallic nanoparticles, 55g of polyurethane resin emulsion, 25g of acrylic resin emulsion, 0.8g of sodium carboxymethyl cellulose, 3g of trimer isocyanate, 4g of polyvinylpyrrolidone, 0.4g of polyoxypropylene glycerol ether, and 60g of water.

[0039] The carbon nanotube-coated silver / cobalt bimetallic nanoparticles were prepared by the following steps: The process was conducted using a thermal plasma device. First, silver micron-sized powder and cobalt micron-sized powder were mixed at a mass ratio of 1:3 and pressed into blocks to serve as the anode catalyst target. A high-purity graphite rod (99.999%) was used as the cathode. The reactor was evacuated to a background vacuum of 5*10⁻⁶. -3 After Pa, methane gas was introduced as a carbon source (partial pressure 0.02 MPa), and argon gas was introduced as a condenser (partial pressure 0.01 MPa). The reaction was carried out for 30 minutes at a working current of 40 amperes and a working voltage of 100 volts. After the reaction was completed, the powder was collected to obtain the target product.

[0040] The flexible electromagnetic shielding film provided in this embodiment is prepared by the following method: (1) Take a 1L empty beaker and add 50g of deionized water. Weigh 4g of polyvinylpyrrolidone (PVP) powder with an analytical balance and add it to the beaker. Stir for 5min to dissolve the PVP powder in the water.

[0041] (2) Add 10g of deionized water to a small beaker, weigh 0.4g of polyoxypropylene glycerol ether and add it to the beaker, then weigh 3g of trimer isocyanate and add it to the small beaker. Stir for 2 minutes to make the polyoxypropylene glycerol ether and trimer isocyanate evenly dispersed in the water. Pour the mixture in the small beaker into the large beaker in step (1) and stir for 2 minutes.

[0042] (3) Weigh 0.8g of sodium carboxymethyl cellulose and add it to a large beaker. Stir for 5 minutes to dissolve it completely. Then weigh 55g of polyurethane resin emulsion and add it to the beaker. Next, weigh 25g of acrylic resin emulsion and add it to the beaker. Stir for 12 minutes to mix all the additives in the large beaker thoroughly. Finally, weigh 18g of carbon nanotube-coated silver / cobalt bimetallic nanoparticles and pour them into the large beaker. Stir for 6 minutes to disperse the nanotubes initially.

[0043] (4) Turn on the power supply of the high pressure homogenizer circulating water, turn on the power supply of the homogenizer, pour the mixture from step (3) into the feed cup of the homogenizer, turn on the start button, first homogenize without pressure for 30 minutes to eliminate large agglomerates in the mixture, then pressurize at 1100 bar for high pressure dispersion for 60 minutes until the homogenized liquid appears mirror black and shiny, then stop the dispersion; export the homogenized dispersion slurry for later use.

[0044] (5) Turn on the coating machine and the vacuum switch. Place the PET film on the coating machine worktable, adjust the gap between the doctor blade and the PET film, pour the dispersed slurry onto the PET film, and turn on the coating button to coat the slurry. Turn on the heating button to heat the PET film to 95°C and dry the slurry for 15 minutes. Remove the dried PET film and peel off the coating layer on its surface to obtain the flexible electromagnetic protective film prepared in this embodiment, with a thickness of 1.7 mm. Example 4

[0045] The composition of the electromagnetic wave absorbing finishing liquid and the preparation method of the flexible electromagnetic shielding film in Example 4 are the same as in Example 2. The thickness of the flexible electromagnetic shielding film is 1.7 mm.

[0046] The preparation method of carbon nanotube-coated silver / cobalt bimetallic nanoparticles in Example 4 differs from that in Example 2 only in that the working current used in Example 4 is 50 amperes and the working voltage is 110 volts. Everything else is the same as in Example 1. Example 5

[0047] The composition of the electromagnetic wave absorbing finishing liquid and the preparation method of the flexible electromagnetic shielding film in Example 5 are the same as in Example 2. The thickness of the flexible electromagnetic shielding film is 1.7 mm.

[0048] The preparation method of carbon nanotube-coated silver / cobalt bimetallic nanoparticles in Example 5 differs from that in Example 2 only in that the working current used in Example 5 is 10 amperes and the working voltage is 80 volts. Everything else is the same as in Example 1.

[0049] Comparative Example 1 Comparative Example 1 uses carbon nanotube-coated silver nanoparticles instead of the carbon nanotube-coated silver / cobalt bimetallic nanoparticles of Example 2. The carbon nanotube-coated silver nanoparticles are prepared through the following steps: The experiment was conducted using a thermal plasma apparatus. First, a silver micron powder briquette with a total mass equal to that of the silver-cobalt mixed powder from Example 2 was used as the anode catalyst target, and a high-purity graphite rod (99.999%) was used as the cathode. The reactor was evacuated to a background vacuum of 5*10⁻⁶. -3 After Pa, methane gas was introduced as a carbon source (partial pressure 0.02 MPa), and argon gas was introduced as a condenser (partial pressure 0.01 MPa). The reaction was carried out for 30 minutes at a working current of 30 amperes and a working voltage of 95 volts. After the reaction was completed, the powder was collected to obtain carbon nanotube-coated silver nanoparticles.

[0050] The component contents of the electromagnetic wave absorbing finishing liquid in Comparative Example 1 and the preparation method of the flexible electromagnetic shielding film were the same as in Example 2. The thickness of the flexible electromagnetic shielding film was 1.7 mm.

[0051] Comparative Example 2 Comparative Example 2 uses cobalt-coated carbon nanotube nanoparticles instead of the silver / cobalt bimetallic carbon nanotube nanoparticles of Example 2. The cobalt-coated carbon nanotube nanoparticles are prepared through the following steps: The experiment was conducted using a thermal plasma apparatus. First, a cobalt micron-sized powder briquettes with a total mass equivalent to the silver-cobalt mixed powder from Example 2 were used as the anode catalyst target, and a high-purity graphite rod (99.999%) was used as the cathode. The reactor was evacuated to a background vacuum of 5*10⁻⁶. -3 After Pa, methane gas was introduced as a carbon source (partial pressure 0.02 MPa), and argon gas was introduced as a condenser (partial pressure 0.01 MPa). The reaction was carried out for 30 minutes at a working current of 30 amperes and a working voltage of 95 volts. After the reaction was completed, the powder was collected to obtain cobalt-coated carbon nanotube nanoparticles.

[0052] The composition of the electromagnetic wave absorbing finishing liquid in Comparative Example 2 and the preparation method of the flexible electromagnetic shielding film were the same as in Example 2. The thickness of the flexible electromagnetic shielding film was 1.7 mm.

[0053] The reflection loss of the material was tested in a microwave anechoic chamber. The chamber mainly consists of an antenna horn, an absorbing cone, a vector network analyzer, and a sample stage. The testing range is 2-18 GHz. After placing an 18×18 cm sample on the sample stage, the equipment was started to measure the reflection loss. The main principle is that electromagnetic waves (incident angle of 10 degrees) are emitted from the antenna horn, incident on the sample, and reflected. The reflected electromagnetic waves are received by another antenna horn. The signals from both ends are processed by the connected vector network analyzer to obtain the reflection loss of the sample, which is given in decibels (dB). The resulting reflection loss (RL) curve is shown below. Figure 3 As shown, the specific data is shown in Table 1.

[0054] Table 1. Minimum reflection and effective bandwidth of the flexible electromagnetic shielding films prepared in the examples and comparative examples. Minimum reflection (dB) -38.37 -41.83 -40.38 -38.77 -36.45 -27.97 -29.63 Effective bandwidth (GHz) 5.6 7.1 5.7 5.3 5.4 3.3 4.3 The comparison of Examples 1-5 shows that the working current and voltage have a significant impact on the morphology and composition of the final carbon nanotube-coated silver / cobalt bimetallic nanoparticles during the preparation process, which in turn affects the absorption performance of the final electromagnetic shielding film. Among them, Example 2 has the best current and voltage parameters, with a minimum reflection of -41.83 dB and an effective bandwidth of 7.1 GHz.

[0055] In Comparative Example 1, the carbon nanotubes are only coated with silver, resulting in excessively high electrical conductivity and "impedance mismatch." This causes a large number of electromagnetic waves to be directly reflected at the film surface, unable to penetrate the material's interior, thus resulting in poor reflection loss and narrow bandwidth. In Comparative Example 2, the carbon nanotubes are only coated with cobalt, lacking high conductivity and failing to provide sufficient dielectric loss, thus limiting the overall electromagnetic attenuation capability. Furthermore, Comparative Examples 1-2 lack the absorption effect generated by heterogeneous interfaces such as carbon-silver, carbon-cobalt, and silver-cobalt, therefore their absorption performance is poor.

[0056] All aspects, embodiments, and features of this invention should be considered illustrative in all respects and not limiting of the invention; the scope of the invention is defined only by the claims. Other embodiments, modifications, and uses will become apparent to those skilled in the art without departing from the spirit and scope of the invention as claimed.

[0057] In the preparation method of this invention, the order of the steps is not limited to the listed order. For those skilled in the art, variations in the order of the steps without creative effort are also within the scope of protection of this invention. Furthermore, two or more steps or actions can be performed simultaneously.

[0058] Finally, it should be noted that the specific embodiments described herein are merely illustrative examples of the invention and are not intended to limit the implementation of the invention. Those skilled in the art can make various modifications or additions to the described specific embodiments or use similar methods to replace them; it is neither necessary nor possible to exemplify all embodiments here. However, these obvious variations or modifications derived from the essential spirit of the invention still fall within the scope of protection of the invention, and interpreting them as any additional limitation would contradict the spirit of the invention.

Claims

1. An electromagnetic wave absorbing finishing liquid, characterized in that, By weight, it includes the following components: 10-20 parts of carbon nanotube-coated silver / cobalt bimetallic nanoparticles, 50-60 parts of polyurethane resin emulsion, 20-30 parts of acrylic resin emulsion, 0.5-1 part of sodium carboxymethyl cellulose, 2-4 parts of curing agent, 2-5 parts of polyvinylpyrrolidone, 0.1-0.5 parts of defoamer, and water. The carbon nanotube-coated silver / cobalt bimetallic nanoparticles were prepared by the following method: The reaction is carried out in a thermal plasma device. A mixture of silver and cobalt powder is pressed into a block and used as the anode catalyst target. A high-purity graphite rod with a purity of ≥99.99wt% is used as the cathode. The system is evacuated, and then a carbon source and condensate gas are introduced to maintain the working pressure ≤0.05MPa. The thermal plasma reaction is carried out under the conditions of working current 20-40A and voltage 90-100V. After the reaction is completed, the product is collected to obtain carbon nanotube-coated silver / cobalt bimetallic nanoparticles. The carbon source is one or more of ethanol, methane, ethylene, and acetylene.

2. The electromagnetic wave absorbing finishing liquid according to claim 1, characterized in that, The curing agent is one or more mixtures of isocyanate, 1,4-butanediol and polyether polyol; And / or, the defoamer is one or more mixtures of emulsified silicone oil, polyoxypropylene glycerol ether, polyoxypropylene polyoxyethylene glycerol ether, and polydimethylsiloxane.

3. The electromagnetic wave absorbing finishing liquid according to claim 1, characterized in that, The solid content of the polyurethane resin emulsion is 20-50 wt%, and the solid content of the acrylic resin emulsion is 20-50 wt%.

4. The electromagnetic wave absorbing finishing liquid according to claim 1, characterized in that, The average particle size D50 of silver powder and cobalt powder is 10~50μm, respectively; the mass ratio of silver powder to cobalt powder is 1:1~4.

5. The electromagnetic wave absorbing finishing liquid according to claim 1, characterized in that, The condenser gas is argon and / or helium; the partial pressure of the carbon source is 0.02~0.04 MPa, the partial pressure of the condenser gas is 0.01~0.02 MPa, and the thermal plasma reaction time is 10~60 min.

6. The electromagnetic wave absorbing finishing liquid according to claim 1, characterized in that, In carbon nanotube-coated silver / cobalt bimetallic nanoparticles, the particle size range of silver and cobalt particles is 1~20 nm.

7. The method for preparing an electromagnetic wave absorbing finishing liquid as described in claim 1, characterized in that, Includes the following steps: (1) Dissolve polyvinylpyrrolidone in water and stir until homogeneous; (2) Disperse the defoamer and curing agent in water and stir until homogeneous; (3) Pour the mixture from step (2) into the mixture from step (1), add sodium carboxymethyl cellulose to dissolve it completely; add polyurethane resin emulsion and acrylic resin emulsion in sequence and mix evenly; finally add carbon nanotube-coated silver / cobalt bimetallic nanoparticles and stir to disperse them initially. (4) The above mixture is subjected to high pressure homogenization to obtain a uniformly dispersed slurry, which is the electromagnetic wave absorption finishing liquid.

8. The preparation method according to claim 7, characterized in that, The high-pressure homogenization process includes: first, homogenizing without pressure for 10-40 minutes, then pressurizing to 800-1800 bar and dispersing under high pressure for 20-80 minutes.

9. A flexible electromagnetic protective film, characterized in that, It is prepared using the electromagnetic wave absorbing finishing liquid described in claim 1, and the preparation method includes the following steps: (1) Dissolve polyvinylpyrrolidone in water and stir until homogeneous; (2) Disperse the defoamer and curing agent in water and stir until homogeneous; (3) Pour the mixture from step (2) into the mixture from step (1), add sodium carboxymethyl cellulose to dissolve it completely; add polyurethane resin emulsion and acrylic resin emulsion in sequence and mix evenly; finally add carbon nanotube-coated silver / cobalt bimetallic nanoparticles and stir to disperse them initially. (4) The above mixture is subjected to high-pressure homogenization to obtain a uniformly dispersed slurry, which is the electromagnetic wave absorption finishing liquid. (5) Apply the electromagnetic wave absorbing finishing liquid onto the substrate and dry it. The resulting coating layer is the flexible electromagnetic protection film.

10. The application of the flexible electromagnetic shielding film as described in claim 9 in electromagnetic radiation protection products.